Internet Gaming Disorder and Aggression: A Cross-Sectional Study - Ambreen, Farhana; Fatima, Ambreen; Amin, Rizwana (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: The prevalence of Internet gaming disorder (IGD) is growing on a global scale, leading to heightened concerns around adolescents’ aggressiveness. The presence of competition and lack of supervision in online gaming might provoke aggressive tendencies. Adolescents might be influenced by competitive games and interactions. Pakistan, a country with advanced technology, has limited investigations on issues related to IGD and aggressiveness. This cross-sectional study examines IGD and aggression in adolescent boys (N = 240) and girls (N = 136) who play online games, recruited via a convenient sampling technique. The study also examines the aggression of gamers (G1) and non-gamers (G2). The results of two-way ANOVA show that adolescent boys and girls differ in IGD and Aggression scores with the evidence of the significance of the main effect for the assessment of IGD with F(1.374) = [6.362], p = .014. In addition, results indicated evidence of the significance of the main effect for the assessing aggression with F(1.374) = [6.645], p = .010. Further results of mixed factorial ANOVA indicated significant differences in the aggression of G1 and G2, male and female participants with the significant main effect of aggression with F(1.374) = [49.530], p < .001. The findings emphasize the importance of monitoring and regulating adolescents’ gaming behaviors, especially excessive gaming. Parents, educators, and healthcare professionals can help identify adolescents at risk of IGD and provide appropriate support and therapies. Promoting appropriate gaming habits and preventing the detrimental effects of excessive gaming in adolescents is essential.